Power system modeling and simulation - Luo, Yishi (Nanyang Technological University, 2020)
Nowadays, world-wide electrical power systems tend to be more complicated with the penetration of renewable energy as well as the structural diversity resulting more unpredictable contingences for regulators and engineers to analyze and settle. Hence, to better characterize system under contingency situations, new methods of simulation to system is acquired urgently for improving planning and enhancing operation of electrical power system, therefore, establishing reasonable and effective models seems to be a good approach. Now power system becomes a diversification carrier with more variety of elements and features. Correspondingly, the demand for higher functional software with better modeling environment is acquired. In this dissertation, PSS/E and MATLAB/Simulink environment are appliedintegratedly, the dissertation is mainly focusing on a test system called Nordic-74 which is a variant of Nordic-32 published by IEEE Power & Energy Society in 2015. The dissertation initially develops a equivalent model under steady state and dynamic state with implement of parameters from PES-TR19, then the power flow calculation and dynamic contingency analysis including overloading, underloading, tripping of tie lines and changes in load composition are proceeded, finally, the white paper emphasizes on analyzing the rotor angle, frequency, voltage stability of some elements including generators, bus bars in Nordic-74 test system. Through building and analyzing the Nordic-74 model, people are able to better make a clear recognition of interconnected huge power system. Key words: Nordic-74, PSS/E, Simulation, model, Dynamic analysis, Rotor angle stability, Voltage stability, Frequency stability.